Design and feasibility analysis of a new completion monitoring technical scheme for natural gas hydrate production tests - Qiu-ping Lu; Yan-jiang Yu; Xie Wen-wei; Jin-qiang Liang; Jing-an Lu; Ben-chong Xu; Hao-xian Shi; Hao-yu Yu; Ru-lei Qin; Xing-chen Li; Bin Li (China Geology)
ABSTRACT: As a prerequisite and a guarantee for safe and efficient natural gas hydrates (NGHs) exploitation, it is imperative to effectively determine the mechanical properties of NGHs reservoirs and clarify the law of the change in the mechanical properties with the dissociation of NGHs during NGHs production tests by depressurization. Based on the development of Japan’s two offshore NGHs production tests in vertical wells, this study innovatively proposed a new subsea communication technology—accurate directional connection using a wet-mate connector. This helps to overcome the technical barrier to the communication between the upper and lower completion of offshore wells. Using this new communication technology, this study explored and designed a mechanical monitoring scheme for lower completion (sand screens). This scheme can be used to monitor the tensile stress and radial compressive stress of sand screens caused by NGHs reservoirs in real time, thus promoting the technical development for the rapid assessment and real-time feedback of the in-situ mechanical response of NGHs reservoirs during offshore NGHs production tests by depressurization.©2023 China Geology Editorial Office.